Building a Community-Academic Partnership: Implementing a Community-Based Trial of Telephone Cognitive Behavioral Therapy for Rural Latinos. (19th September 2012) - Aisenberg, Eugene; Dwight-Johnson, Meagan; O'Brien, Mary; Ludman, Evette J.; Golinelli, Daniela
Abstract : Concerns about the appropriate use of EBP with ethnic minority clients and the ability of community agencies to implement and sustain EBP persist and emphasize the need for community-academic research partnerships that can be used to develop, adapt, and test culturally responsive EBP in community settings. In this paper, we describe the processes of developing a community-academic partnership that implemented and pilot tested an evidence-based telephone cognitive behavioral therapy program. Originally demonstrated to be effective for urban, middle-income, English-speaking primary care patients with major depression, the program was adapted and pilot tested for use with rural, uninsured, low-income, Latino (primarily Spanish-speaking) primary care patients with major depressive disorder in a primary care site in a community health center in rural Eastern Washington. The values of community-based participatory research and community-partnered participatory research informed each phase of this randomized clinical trial and the development of a community-academic partnership. Information regarding this partnership may guide future community practice, research, implementation, and workforce development efforts to address mental health disparities by implementing culturally tailored EBP in underserved communities.